Correlation Between TNFAIP2 Gene Polymorphism and Prediction/Prognosis for Gastric Cancer and Its Effect on TNFAIP2 Protein Expression - Guo, Fang; Xu, Qian; Lv, Zhi; Ding, Han-Xi; Sun, Li-Ping; Zheng, Zhen-Dong; Yuan, Yuan (Frontiers in Oncology, 2020)
Objective: TNFAIP2 is a novel gene induced by TNF-α and as a variety of biological functions such as regulating inflammatory reaction and tumor angiogenesis. This study aims to understand the correlation between TNFAIP2 gene polymorphism and prediction as well as prognosis of gastric cancer (GC) in Chinese population. Methods: One thousand two hundred and seventy-nine cases were enrolled, including 640 GC and 639 non-cancer cases. The functional tagSNPs of TNFAIP2 gene were screened by Haploview software and NIH Snpinfo website. Human whole blood genomic DNA was extracted by phenol chloroform method and analyzed by KASP SNP typing and sequencing method. ELISA was used to determine the expression of TNFAIP2 protein in serum samples. The miRNAs bound to TNFAIP2 3’UTR rs8126 were predicted by MirSNP and TargetScan database. SPSS 22.0 software was used for statistical analysis, and P<0.05 showed statistical difference. Results: Four functional TNFAIP2 tagSNPs were found by bioinformatics analysis. TNFAIP2 rs8126 SNPs could increase GC risk in general population, and the risk in heterozygous patients is higher than that in wild-type patients (P=0.001, OR=1.557). In the dominant model, TNFAIP2 rs8126 polymorphic carriers is 1.419 times higher (P=0.007). However, polymorphism of TNFAIP2 rs710100, TNFAIP2 rs3759571 and TNFAIP2 rs3759573 were not correlated with the risk of gastric cancer in Chinese population. In the subgroup analysis, cases with TNFAIP2 rs8126 heterozygous or mutated type have a higher GC risk in male, aged 60 years or older, H.pylory positive, non-smoking and non-drinking carriers. We found that the expression of TNFAIP2 protein was significantly different between GC patients and healthy people (P=0.029). Five miRNAs that may bind to TNFAIP2 3’UTR rs8126 were predicted, including hsa-mir-3191-3p, hsa-mir-711, hsa-mir-4668-5p, hsa-mir-92b-5p and hsa-mir-184. Conclusion: TNFAIP2 3’UTR rs8126 polymorphism was associated with GC risk in Chinese population. TNFAIP2 protein expression was increased in Chinese GC patients, and TNFAIP2 3’UTR rs8126 polymorphism could affect the expression of TNFAIP2 protein.